Feasibility and Economic Assessment of a Hybrid Energy System for Bakori Area, Katsina in Nigeria - Felix, Agbetuyi Ayoade; Amuta, Elizabeth Oses; Evwieroghene, Orovwode Hope; Ademola, Abdulkareem; Racheal, Amoo; Adegoke, Agbetuyi Oluranti (International Journal of Energy Economics and Policy, 2023)
Electricity is vital to the economic growth any nation, as access to it, is key in achieving economic development. However, a stable electricity supply is lacking in the country, and with the increasing demand, it will be impossible to attain with the current infrastructure. This paper aims to carry out feasibility study of a hybrid energy system (HES) for sustainable power supply in Bakori Local Government Area, Katsina, Nigeria. The simulation results were generated using HOMER (Hybrid Optimization of Multiple Electric Renewables) software utilizing the solar system, and wind generator resources to satisfy the residential energy requirement for the case study. The proposed HES was compared with other configurations in terms of cost and energy production. The simulation results depict that the PV/Wind/Battery system is a viable hybrid energy system with a Net Present Cost of ₦3.62M and an electricity generation of 1,423,132 kWh/yr compared to the other configurations which produce less energy at a higher Net Present Cost.